1997
DOI: 10.1007/bf02464106
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and pharmacological activity of 5-aryl-4-acetyl-1-carboxyalkyl-tetrahydropyrrole-2,3-diones

Abstract: Previously we have reported on the antiinflammatory [1] and antiviral [2] properties of 1,4,5-trisubstituted tetrahydropyrrole-2,3 -diones.tn continuation of the search for biologically active compounds in the series of substituted tetrahydropyrrole-2,3-diones (structurally similar to pyracetam), it was of interest to attempt their synthesis by the method described in [2], using natural co-and 13-amino acids as the amino components, and study the nootropic, antibacterial, antiinflammatory, and analgesic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Previously, we have reported that tetrahydropyrrole-2,3-diones substituted at positions 1, 4, and 5 of the heterocycle possess analgesic [1], nootropic [1], antiinflammatory [2], antibacterial [3], and antiviral activity [4]. In continuation of the search for biologically active compounds in the class of substituted pyrrolidine-2,3-diones, it was also of interest to obtain their 3-hydrazones and to study how this structural change will modify the chemical properties and antibacterial activity of pyrrolidine-2,3-diones.…”
mentioning
confidence: 99%
“…Previously, we have reported that tetrahydropyrrole-2,3-diones substituted at positions 1, 4, and 5 of the heterocycle possess analgesic [1], nootropic [1], antiinflammatory [2], antibacterial [3], and antiviral activity [4]. In continuation of the search for biologically active compounds in the class of substituted pyrrolidine-2,3-diones, it was also of interest to obtain their 3-hydrazones and to study how this structural change will modify the chemical properties and antibacterial activity of pyrrolidine-2,3-diones.…”
mentioning
confidence: 99%
“…Substituted tetrahydropyrrol-2,3-diones are known to have antimicrobial, anti-inflammatory, analgesic, nootropic, and other types of activity [2,3].…”
mentioning
confidence: 99%
“…Previously, we demonstrated that substituted 3-hydroxy-3-pyrrolin-2-ones possess pharmacological activity of various types, including antimicrobial [1 -3], antiinflammatory [4], analgesic [4,5], antiviral [6], and nootropic [3,5] in combination with relatively low toxicity. According to the published data, both the type and magnitude of activity depend on the character of the substituent in position 1 of the heterocycle [3,4].…”
mentioning
confidence: 99%